The Roles of Porous Coral Sands in Initial Enrichment of Ammonia-Oxidizing Bacteria - Qing Guo; Zao-he Wu; Ming-liang Qian; Binhe Gu (The Scientific World Journal)
The purpose of this study was to investigate the roles of coral sands in the enrichment and isolation of ammonium-oxidizing bacteria (AOB). We hypothesized that the porous coral sands provided additional surface area and nutrients for the growth of periphytic AOB. In the present study, an orthogonal test was designed to compare the AOB conversion rates of ammonium-nitrogen (NH4+N) to nitrite-nitrogen (NO2--N) among various combinations of culture media. Results showed that the conversion of NH4+N to NO2--N increased significantly when the coral sands were added, implying that coral sands were beneficial to the growth of AOB. Additions of potassium dihydrogen phosphate (KH2PO4) or sodium bicarbonate (NaHCO3) to the media became unnecessary when coral sands were used, but the addition of KH2PO4 was needed when the molar nitrogen to phosphorus (N:P) ratio reached 10 in the enrichment media using calcium carbonate (CaCO3) powder as a calcium source.